Optimization of the LaBr3 detector model using differential evolution algorithms; Applied Radiation and Isotopes; Vol. 221 - Prozorova I. V. Irina Valentinovna; Sabitova R. Radmila; Bedenko S. V. Sergey Vladimirovich; Irkimbekov R. A. Ruslan Aleksandrovich; Popov Yu. A. Yuriy Anatolevich; Svetachev S. N. Stanislav Nikolaevich; Samarkhanov K. K. Kuanysh Kanatuly (2025, 2025)
Title screen